Keterlibatan Warga Negara dalam Pembangunan Ekonomi Berkelanjutan Melalui Program Jalin Matra: (Studi Kasus di Kelurahan Bandungrejosari Kecamatan Sukun Kota Malang) - Eleonora Bei; Engelbertus Kukuh; Romadhon Romadhon (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
The purpose of this study is to create a society with a decent socio-economic status by describing how citizens participate in sustainable economic growth, namely through the Jalin Matra program. This study employs a case study approach, utilizing a descriptive-qualitative methodology. The data collection methods used are documentation, interviews, and observations. According to the study's findings, (1) one way to increase citizen involvement is to participate in the KRTP (Korean socialization program). Second, companies can receive technical assistance in the form of development, management, and marketing (2) Efforts to establish a sustainable economy encompass management and preservation programs. In this program, households aim to manage productive businesses independently, develop business networks in both the upstream and downstream sectors, implement effective marketing strategies, and ultimately, enhance KRTP social capital through group strengthening. hening. Pancasila and citizenship Education in the Jalin Matra program includes social sciences that focus on humans as members of society and living beings and how they interact with each other. The program involves the grouping of individuals between KRTP and Pokmas managers, as well as their interactions with stakeholders of social institutions.